Fusi Nalar Qur'ani dan Pengetahuan Kontemporer: Implikasinya di Pasar Virtual - Ainul Yaqin (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2020)
Recent fact more exacerbated by arrival of an era called "disruption", one of the revolution is technologies more sophisticated and daily life thick with digitalization. The speed of information is not limited by the layers of space and time show some information and discourse, especially about topic religious and Islamic to disseminated to anyone. It seems to have formed consist of the phenomenon ideological war or dispute in promoting discourse of resurgence. This article means to define how to use utilization information of technology and digital that has been transmitted as a space for ideological contestation that each grabbed the label "moderate"? This research used several theories as analytical tool. First, Karl Marx's conflict theory was used to read and map conflicts about the onslaught of ideological contestation in the disruption era. Second, the Islamic typological theory of M. Abou El-Fadl, which is one of the contemporary thinker used to map paradigm Islamic in recent times. Third, Gadamer's hermeneutic theory (horizon fusion) was used to emerge new meaning about moderate Islamic promotion strategies. The result of this research is to producing a moderate and interesting Islamic ideology, the mastery of science interpretation and also participation in contemporary insight very useful as intellectual and decisive established for giving an Islamic insight. Concerned with strategies in face onslaught of ideological warfare in the virtual market, contemporary strategies can born from ability to dominate in the digital space.